Case report: Hematologic malignancies concomitant diagnosis of hairy cell leukemia and chronic lymphocytic leukemia: A rare association - Valvano, Luciana; D’Auria, Fiorella; Grieco, Vitina; Statuto, Teodora; Nozza, Filomena; Pietrantuono, Giuseppe; Villani, Oreste; D’Arena, Giovanni; Lamorte, Daniela (Frontiers in Oncology, 2022)
A case of concomitant hairy cell leukemia (HCL) and chronic lymphocytic leukemia (CLL) in a 50 years old male was reported. Flow cytometry and droplet digital PCR (ddPCR) to detect the BRAF V600E mutation were used. HCL population was the predominant component. The patient was firstly treated with cladribine and then with rituximab obtaining HCL partial remission. Importantly, the high sensitivity of our flow cytometric approach allowed us the detection of a small population “P3”, in addition to the typical HCL and CLL clones. P3 clone changed over the time passing from a HCL-like to a CLL-like immunophenotype. This case is added to the few other cases of synchronous HCL and CLL already reported in the literature and underlines the importance of analyzing chronic lymphoproliferative disorders by highly sensitive diagnostic techniques, like multicolor flow cytometer and ddPCR, to evaluate the possible association between HCL and CLL at diagnosis.